Science and Religion: Students’ Views and Understanding on Evolutionary Concepts - Timilsena, Narayan Prasad; Devkota, Krishna Maya (AMC Journal, 2022)
This study was carried out to explore the connection between science and religion especially focused on students’ views and understanding of evolutionary concepts of biology at the secondary level. To find out the students’ views and understanding of evolutionary concepts in connection with science and religion, a mixed-method design was used consisting of 50 participants of five secondary schools in Kathmandu Metropolitan City. The random sampling method was used for student selection while purposive sampling was used for schools selection. A five-point Liker scale, concept understanding inventory, and interview guideline tools were developed. The tools were validated for the collection of data. Thus, the gathered data were analyzed through descriptive statistics and thematic explanation. From the analysis, it was found that religion and science are continued debatable subjects in philosophy and theology till now. It also provides a philosophical analysis of how they interrelate with each other. The majority understanding of students has been found to be in conflict, science supportive, religion supportive, coalition, contrast, and supplementary views between science and religion towards evolutionary biology. This study concludes that students have common sense, content and nature of science, non-science, and dialect-based misleading as well as corrected understanding about evolutionary biology. Thus, the creationism concept of evolution should be included in the science curriculum to achieve a better understanding of the evolutionary concept.